Teaching of physics in the context of planetology and habitability in high school: a case of successful online meaningful learning - Alexandre Michaelsen, Gian; Serrano de Andrade Neto, Agostinho (RENOTE, 2021)
The COVID-19 pandemic hastened the development of techniques and didactic sequences for online education, some that promoted learning, others that were lacking. In this contribution we |show how it was possible to achieve Ausubelian meaningful learning in Physics through remote teaching, by having as context planetology and habitability. These concepts may allow the development of expected specific competences described in the Brazilian Common National Curriculum Base (BNCC), that also have substantial media exposure and are possible to be developed in High School. At the end, the students have developed skills that allowed them to determine, based on real data, whether an exoplanet is habitable or not. Using Bardin’s content analysis, it was possible to find evidence of meaningful learning of the intended skills and concepts.